Early F-actin disorganization may be signaling vacuole disruption in incompatible pollen tubes of Nicotiana alata - Goldraij, Ariel (2014)
Self-incompatibility (SI) systems appeared early in plant evolution as an effective mechanism to promote outcrossing and avoid inbreeding depression. These systems prevent self-fertilization by the recognition and rejection of self-pollen and pollen from closely related individuals. The most widespread SI system is based on the action of a pistil ribonuclease, the S-RNase, which recognizes and rejects incompatible pollen. S-RNases are endocyted by pollen tubes and stored into vacuoles. By a mechanism that is still unknown, these vacuoles are selectively disrupted in incompatible pollen, releasing S-RNases into the cytoplasm and allowing degradation of pollen RNA. Recently, we have studied the timing of in vivo alterations of pollen F-actin cytoskeleton after incompatible pollinations. Besides being essential for pollen growth, F-actin cytoskeleton is a very dynamic cellular component. Changes in F-actin organization are known to be capable of transducing signaling events in many cellular processes. Early after pollination, F-actin showed a progressive disorganization in incompatible pollen tubes. However by the time the F-actin was almost completely disrupted, the large majority of vacuolar compartments were still intact. These results indicate that in incompatible pollen tubes F-actin disorganization precedes vacuolar disruption. They also suggest that F-actin may act as an early transducer of signals triggering the rejection of incompatible pollen.